Information and communication technology use in asthmatic patients: a cross-sectional study in Latin America. Issue 3 (12th July 2017) - Calderón, Juan; Cherrez, Annia; Ramón, Germán Darío; Lopez Jove, Orlando; Baptist, Alan; Matos, Edgar; Morfín Maciel, Blanca; Calero, Erick; Sanchez-Borges, Mario; Cherrez, Sofia; Simancas-Racines, Daniel; Cherrez Ojeda, Ivan
Rapid diffusion, low cost and broad availability of information and communication technologies (ICTs) make them an attractive platform for managing care, communication and interventions in asthma. There is little information in Latin America about usage frequency of ICTs in asthmatic patients. The analysis undertaken consisted of an observational, cross-sectional study that aimed to identify the frequency and type of ICTs most often used by asthmatics. The Spanish version of the Michigan questionnaire was employed in five Latin American countries. Age and educational level was categorised. Logistic regression was performed among these groups concerning the frequency of ICT usage and the level of interest shown in seeking and receiving information about asthma. In total, 673 asthma patients were surveyed. The mean age was 43.44 years. Over two-thirds of the participants were female (68.4%). The most used ICT was the short message service (SMS) (69.9%). SMS and E-mail are useful tools for communicating ( i.e. receiving and seeking information) with all asthma patients, irrespective of their age. WhatsApp (61.5%) and Facebook (32.0%) were rated as being the most interesting channels of communication for receiving information. Regression analysis showed that younger asthmatics and asthmatics with higher educational levels were most likely to use almost all forms of ICTs. ICTs are generally an attractive platform for managing care, communication and interventions to improve asthma care. SMS and E-mail were found to be the preferred ICT forms among users. However, social media forms such as WhatsApp and Facebook may also be appropriate for certain types of patient. ICT and social media use among asthmatics from Latin America http://ow.ly/TxVj30cKylJ